Model of heterotransistor with quantum dots - Timofeyev, V.I.; Faleyeva, E.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Heterostructure transistors with quantum dots (QD) are now very perspective devices because of their higher velocities of electrons in the channel. Simulation results for concentration and carrier velocity distributions depending on the QD size, concentration and location were presented in this paper. It is shown that presence of QD in the channel causes a significant increase of current. Also, QD location and concentration influence to the output characteristics of transistor was established.